Patient Radiation Doses in Interventional Cardiology Procedure - E. Hiswara; D. Kartikasari; N. Nuraeni; H. Sofyan; K. Y. P. Sandy (Atom Indonesia, 2022)
Interventional cardiology is a minimally-invasive imaging procedure that allows medical doctor to evaluate and treat structural heart diseases. Due to its main advantages of avoidance of the scars and pain, as well as long post-operative recovery, interventional cardiology procedures have rapidly been growing. However, the increasingly complex and time-consuming procedures in interventional cardiology may increase the radiation exposure received by patients. This paper describes a study to measure patient radiation doses in terms of air kerma and kerma air-product (KAP) for various types of interventional cardiology procedures conducted in Indonesia. The measurements were performed at the interventional cardiology or cardiac catheterization facilities in sixteen hospitals in ten cities in Indonesia during the years of 2015 to 2019. A total of 147 procedures conducted on adult patients were used in this study. The type of procedure, total KAP, and air kerma were recorded after each procedure was completed. The demographic data of the patients were also recorded. The results showed that the mean air kerma and KAP measured for CA (coronary angiography) procedure were 680.73±57.85 mGy and 12.52±5.86 Gy cm2, respectively, while the values for PCI (percutaneous coronary intervention) procedure were 890.66±38.76 mGy and 20.18±9.37 Gy cm2, respectively. These results are well within the ranges reported by other previous studies. The results are somewhat affected by the     body mass index of patients, while the fatal cancer risks among patients of CA and PCI procedures are comparable with those among interventional radiology procedures patients.